A copula-based approach for generating lattices - Wang, Tianyang, author; Dyer, James S., author; Hahn, Warren J., author; Review of Derivatives Research, publisher (Colorado State University. Libraries, 2015)
Discrete approximations such as binomial and trinomial lattices have been developed to model the intertemporal dynamics of variables in a way that also allows contingent decisions to be included at the appropriate increments in time. In this paper we present an approach for developing these types of models based on copulas. In addition to ease of implementation, a primary benefit of this approach is its generality, and we show that various binomial and trinomial approximation methods for valuing contingent claim securities in the literature are special cases of this approach, each based on a choice of a particular set of probability and/or branching parameters. Because this approach encompasses these and other cases as feasible solutions, we also show how it can be used to optimize the construction of lattices so that discretization error is minimized, and we demonstrate its application for an option pricing example.
Published as: Review of Derivatives Research, vol. 18, no. 3, July 2015, pp.263–289, https://doi.org/10.1007/s11147-015-9111-x.
Keywords: discrete models; stochastic processes; option pricing; copulas